2016
DOI: 10.1177/1744806916679166
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal activation of microglia may underlie the shared neurobiology of comorbid posttraumatic stress disorder and chronic pain

Abstract: The high comorbidity rates of posttraumatic stress disorder and chronic pain have been widely reported, but the underlying mechanisms remain unclear. Emerging evidence suggested that an excess of inflammatory immune activities in the hippocampus involved in the progression of both posttraumatic stress disorder and chronic pain. Considering that microglia are substrates underlying the initiation and propagation of the neuroimmune response, we hypothesized that stress-induced activation of hippocampal microglia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 59 publications
(97 reference statements)
5
43
0
1
Order By: Relevance
“…The qPCR and IHC results indicated that IFS increased the level of mRNA of iba-1, the number of Iba-1-positive cells and changed the morphology of the microglia from hyper-ramified to amoeboid shape in the PFC and hippocampus. Consistent with our results, Sun et al also found up-regulation of Iba-1 in the CA1 and CA3 regions of the hippocampus in the animal model of PTSD induced by single prolonged stress ( 36 ). Similarly, other studies also reported that various stressors could induce microglial activation in different animal models ( 39 42 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The qPCR and IHC results indicated that IFS increased the level of mRNA of iba-1, the number of Iba-1-positive cells and changed the morphology of the microglia from hyper-ramified to amoeboid shape in the PFC and hippocampus. Consistent with our results, Sun et al also found up-regulation of Iba-1 in the CA1 and CA3 regions of the hippocampus in the animal model of PTSD induced by single prolonged stress ( 36 ). Similarly, other studies also reported that various stressors could induce microglial activation in different animal models ( 39 42 ).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have reported that a single dose of minocycline had a potential effect of preventing the deterioration of behavior and exaggeration of neuroinflammation ( 14 ). Similarly, a longer injection of minocycline also attenuated single prolonged stress-induced anxiety-like behavior ( 36 ). In addition, minocycline was able to improve cognitive deficits in a cerebral microvascular amyloid model ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also evidence that glial processes may contribute to post-SPS dysfunction and poor behavioral recovery. For example, microglial activation caused by glucocorticoid signaling in the spinal cord ( 288 , 347 ) and HC ( 348 ) appears to contribute to post-SPS hyperalgesia. Immunohistochemical data indicate that glial cell number is decreased in the HC in a time-dependent manner following SPS, and magnetic resonance spectroscopy findings of decreased choline in the HC ( 312 ) and creatine in the HC ( 312 ) and mPFC ( 154 ) are consistent with a glial-related mechanism ( 312 ).…”
Section: Neural and Molecular Mechanisms In Spsmentioning
confidence: 99%
“…Interestingly, minor recurrent trauma like concussion during sport (boxing, soccer, etc. ), or injury in a distal CNS region, may also activate microglia in otherwise healthy tissue and result on a longer term in substantial mental disease or chronic pain [ 246 , 247 ]. One has also to consider that injury breaks down the BBB and allows immigration of blood derived immune cells, including macrophages and lymphocytes that contribute to the acute inflammatory reaction and subsequent tissue repair [ 16 , 248 ].…”
Section: Introductionmentioning
confidence: 99%